The Effect of Maceration and Soxhletation Extraction Methods on The Flavonoid Content of Anting-anting Leaves Extracts (Acalypha indica L.) Using Uv-Vis Spectrophotometry - Dita Intan Karisma; Christina Indriasari (Universitas STRADA Indonesia, 2023)
Anting-anting (Acalypha indica L) is an annual plant that reaches 30 to 50 cm in height. This plant is often found on mountain slopes, along roadsides, and meadows. Anting-anting leaves (Acalypha indica L) have anti-inflammatory, antibacterial, and antifungal activities. The high content of flavonoids in the leaves of the earrings is efficacious as an antioxidant. This study aims to determine the effect of maceration and soxhletation extraction methods on the levels of flavonoids in the leaves of the anting-anting. This type of research is an experimental study conducted with two extraction methods using 96% ethanol. Qualitative analysis was carried out by color reaction test while quantitative analysis was carried out using a UV-Vis spectrophotometer with the calorimetry method. The standard solution used was quercetin to measure the levels of flavonoids. The results showed that the average level of flavonoids in soxhletation extraction was 5.2266%w/b and in maceration extraction was 5.0084%w/b. The data were tested using the Independent Sample T Test showing a significance value of 0.097 (> 0.05), meaning that there was no significant effect between the maceration and soxhletation extraction methods.